Experimental perfusion device for preservation of donor’s liver - S. F. Bagnenko; O. N. Reznik; A. E. Skvortsov; A. V. Lopota; N. A. Gryaznov; V. V. Kharlamov; G. S. Kireeva (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors aimed to develop complex perfusion medical device in order to successfully maintain viability of donor liver until transplantation. MATERIAL AND METHODS. Experimental perfusion device for normothermic perfusion donor’s liver was developed and tested in the Central Research and Experimental-design Institute of Robotics and Technical Cybernetics. RESULTS. The pre-clinical tests were performed on porcine liver. It was demonstrated that normothermic machine perfusion could restore liver function after 30 minutes of warm ischemia time and provide normalization of biochemical parameters of organ functioning.